Two-Dimensional DDA Contact Constitutive Model for Simulating Rock Fragmentation - Jiao, Yu-Yong; Zhang, Xiu-Li; Zhao, Jian (Journal of engineering mechanics, 2012)
Due to the difficulties of fracture mechanics in dealing with multicrack problems, the continuum-based numerical methods always encounter mathematical problems when modeling rock fragmentation, so the alternative discontinuum-based numerical approaches are worth trying. This paper presents a new two-dimensional contact constitutive model for the discontinuous deformation analysis (DDA) method to simulate the fragmentation of jointed rock. This contact constitutive model consists of a two-phase force-displacement relation in the nomal direction and the Mohr-Coulomb criterion in the shear direction. The two-phase force-displacement relation is imposed in the normal direction of the block interface, instead of the penalty contacting spring. The first phase functions as the original penalty spring, and the second phase serves as a cohesive component. This new contact constitutive model was incorporated into the original DDA code, and four examples were computed for verification. The simulated results agree favorably with those obtained from physical tests and other numerical simulation, showing that the proposed method can simulate the whole process of rock fragmentation and can deal with cases of intact rock, rock mass with nonpenetrative joints, and even blocky rock structures. Furthermore, due to the nature of the triangular block shape, the proposed model can avoid the mesh dependence problem.